The Teaching and Learning Process of Writing Narrative Text during The Pandemic in EFL Class (RETAIN, 2023)
As one of the important skills of the four main skills of English, every student is required to have good writing skill. The pandemic which is caused by the corona virus has made the entire process of learning to write virtually. Condition that suddenly change certainly have various effect in learning to write. Therefore, this study aims to explain how the process of teaching and learning writing skill especially narrative text in the current pandemic era. The object of this study is the result of an observation and interview process conducted to one of the third grade English teachers and twenty-four students taught by that teacher. The researcher also provided questionnaires as a complementary instrument to complement the data obtained from observation and questionnaires before. This study uses a qualitative approach. The result of this study indicate that in every part of teaching and learning process, both teacher and students experienced from the various challenges and difficulties in conducting learning writing narrative text. Not only that, from the various challenges and difficulties in conducting teaching and learning process of writing narrative text, the researcher also found out the right solution to solve the challenges and difficulties they faced in online learning in pandemic era. Keywords: writing skill, Pandemic era, EFL Class.